Исследование характеристик твердоксидных топливных элементов с YSZ/CGO электролитом - Ковальчук А. Н. Анастасия Николаевна; Лебединский А. М. Алексей Михайлович; Соловьёв А. А. Андрей Александрович; Легостаев В. Н. Виктор Никифорович; Ионов И. В. Игорь Вячеславович; Смолянский Е. А. Егор Александрович; Шипилова А. В. Анна Викторовна; Лаук А. Л. Александр Лукьянович (2016, 2016)
Заглавие с экрана